2022
DOI: 10.3390/cancers14122928
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance in Colorectal Cancer: From Mechanism to Clinic

Abstract: Colorectal cancer (CRC) is one of the leading causes of death worldwide. The 5-year survival rate is 90% for patients with early CRC, 70% for patients with locally advanced CRC, and 15% for patients with metastatic CRC (mCRC). In fact, most CRC patients are at an advanced stage at the time of diagnosis. Although chemotherapy, molecularly targeted therapy and immunotherapy have significantly improved patient survival, some patients are initially insensitive to these drugs or initially sensitive but quickly beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 336 publications
0
36
0
Order By: Relevance
“…NONHSAT024276 and PTBP1 produced cascade amplification and mutual restraint effects via the feedback loop. Feedback loops are important and common in the occurrence and development of tumors 30,31 . ncRNAs may sometimes be involved in complicated feedback mechanisms 32 .…”
Section: Discussionmentioning
confidence: 99%
“…NONHSAT024276 and PTBP1 produced cascade amplification and mutual restraint effects via the feedback loop. Feedback loops are important and common in the occurrence and development of tumors 30,31 . ncRNAs may sometimes be involved in complicated feedback mechanisms 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The autophagic machinery is an intracellular degradation system mediated by the fusion of double‐membrane vesicles called autophagosomes, enveloping cytoplasmic components and organelles, to lysosomes to form autolysosomes, which degrade the encased contents 26,34,35 . In cancer biology, autophagy plays dual roles in tumor promotion and suppression, and contributes to cancer cell development and proliferation 26,35,36 . Several anticancer drugs, e.g., 5‐FU and cisplatin, can regulate autophagy 37–40 .…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 34 , 35 In cancer biology, autophagy plays dual roles in tumor promotion and suppression, and contributes to cancer cell development and proliferation. 26 , 35 , 36 Several anticancer drugs, e.g., 5‐FU and cisplatin, can regulate autophagy. 37 , 38 , 39 , 40 Similarly, several studies have reported that autophagy plays an important role in drug sensitivity and resistance to 5‐FU.…”
Section: Discussionmentioning
confidence: 99%
“…MDSC levels were found to be positively correlated with cancer growth and progression, and their presence commonly reduces the efficiency of immunotherapies [ 69 ]. Some of the immune suppressive factors in the TME must be eliminated for cancer immunotherapy to be more effective [ 6 , 69 , 70 ]. Recently, several studies have described the use of different small molecules, nucleotides, conjugates, vitamins, and immunotherapeutic modalities, which are able to inhibit the suppressive activity of MDSCs in cancers [ 42 , 71 , 72 ], and achieve superior immunotherapeutic tumor control by radiotherapy [ 73 ].…”
Section: Targeting Mdscsmentioning
confidence: 99%